Periodontitis in diabetic patients: prevalence, glycemic associations and renal implications-a cross-sectional study - Sil, Shiladitya; Mukherjee, Saswati; Ghosh, Rupa; Ghosh, Chandreyee; Dutta, Soumyajit; Biswas, Chhanda (International Journal of Research in Medical Sciences, 2026)
Background: Diabetes mellitus is associated with multiple systemic complications, including periodontal disease. The bidirectional relationship between diabetes and periodontitis is well established, and emerging evidence suggests periodontal disease may contribute to diabetic nephropathy progression through shared inflammatory mechanisms. This study evaluated the prevalence and severity of periodontitis in diabetic patients and assessed its associations with glycemic control and renal function. Methods: This observational, cross-sectional study enrolled 203 diabetic patients at IPGMER and SSKM Hospital, Kolkata, India (February 2014–August 2015). Periodontal status was assessed using the community periodontal index (CPI) and classified as no, low-grade, or high-grade periodontitis. Clinical parameters including HbA1c, fasting and postprandial plasma glucose, urine albumin-creatinine ratio (ACR), and estimated glomerular filtration rate (eGFR) were recorded. Statistical analysis used was statistical package for the social sciences (SPSS) (p<0.05). Results: Periodontitis prevalence was 85.2%, with high-grade disease in 52.7% and low-grade in 32.5% of participants. Patients with HbA1c ≥8% had significantly greater periodontal severity (p<0.0001). Severe periodontitis was independently associated with higher albuminuria (ACR: 810.94 versus 96.13 mg/g; p=0.0014) and reduced eGFR (73.89 versus 93.13 ml/min/1.73 m²; p=0.0018). Diabetes duration, smoking, and BMI were also significantly associated with periodontal severity. Conclusions: Periodontitis is highly prevalent in diabetic patients and significantly associated with suboptimal glycemic control and renal dysfunction. These findings support integrating periodontal evaluation into routine diabetes management. Prospective studies are needed to determine whether periodontal treatment can mitigate diabetic complications.